Expression of Neurotrophin-3 and trkC following Focal Cerebral Ischemia in Adult Rat Brain with Treadmill Exercise. (6th September 2017) - Chung, Jin-Young; Kim, Min-Wook; Im, Wooseok; Hwang, In Koo; Bang, Moon-Suk; Kim, Manho
Abstract : Neurotrophin-3 (NT-3) is a neurotrophic factor that mainly binds to the tyrosine kinase C (trkC) receptor. NT-3 has been shown to have neuroprotective effects in focal cerebral ischemia. Exercise also has ability to induce functional recovery in focal cerebral ischemia. However, the relationship between NT-3, its receptor trkC, and exercise has not been revealed. In this study, we assessed the expressions of NT-3 and trkC in focal cerebral ischemia. We also assessed the expression of NT-3 and trkC with treadmill exercise in focal cerebral ischemia. The results showed that, in a permanent middle cerebral artery occlusion rat model, exercise increased NT-3 and trkC expression. However, the patterns of expression of NT-3 and trkC at different time points varied. These results suggest that exercise-induced functional recovery in focal cerebral ischemia was related to NT-3 and trkC, but the role on times of NT-3 and trkC differed, although trkC is the receptor kinase for NT-3.